Interval Estimation for the Parameters of the Modified Weibull Distribution Model with Censored Data: a Simulation Study - Perdoná, G.C.; Louzada Neto, F. (Trends in Computational and Applied Mathematics, 2008)
Expressing the lifetime behavior through its hazard enables us to derive special classes of failure distributions according to the hazard pattern. The usual lifetime distributions, as both exponential and Weibull models, accommodate constant (exponential) and increasing/decreasing (Weibull) hazard functions. Nevertheless, in practice, it is common to find lifetime data with hazard function of different types, for example, a U-shaped hazard function. In the present paper we investigate the properties of the modified Weibull model [8], a three-parameter model which allows U-shaped hazards to be accommodated. Inferences for this model’s parameters based on both complete and censored samples are presented. We discuss different parametrizations as well as the interval estimation for the parameters of this model.